Feature-Based Coding System: A New Way of Characterizing Hypnosis Styles - Varga, Katalin; Kekecs, Zoltán (International journal of clinical and experimental hypnosis, 2015)
In this pilot study, the authors introduce a new system to assess hypnosis style. The Feature-Based Coding System (FBCS) comprises 24 standard individual hypnosis sessions, which were videotaped and coded according to both a previous and the new coding system. In addition, both subjects and hypnotists filled the Archaic Involvement Measure (AIM), the Phenomenology of Consciousness Inventory (PCI), and the Dyadic Interactional Harmony Questionnaire (DIH). The interrater agreement of FBCS was good and the construct Maternal-Paternal Axis had a good internal consistency (α = .95). Construct validity was also supported by the findings. Based on these results, a larger scale study is warranted to further establish the reliability and usefulness of this tool.